A spatial phase modulation laser interferometer. (October 2019) - Chen, Ke; Wang, Zelin; Guo, Min; Wang, Xiaona; Liu, Bowen; Wang, Yuming; Wang, Yinbo; Wang, Senyuan; Jin, Jiarong; Yu, Qingxu
Highlights: A simple spatial phase modulation laser interferometer (SPMLI) is presented. The reflected beams from the upper and lower surfaces of the transparent plate produce two-beam interference. The spatial frequency of the image is proportional to the wave number of the laser light and the thickness of the transparent plate. The proposed interferometer can be used for wavelength and thickness measurements. The proposed interferometer has the advantages of simple structure, low cost and no need for mechanical scanning components. Abstract: We propose and realize a spatial phase modulation laser interferometer (SPMLI), which mainly consists of a laser source, an optical fiber, a transparent plate and a linear charge coupled device (CCD). The reflected beams from the upper and lower surfaces of the transparent plate produce two-beam interference. The generated spatial phase modulation interference image is taken by the CCD. The spatial frequency of the image is proportional to the wave number of the laser light and the thickness of the transparent plate. Experimental results show that the wavelength and thickness can be measured in picometer-level and nanometer-level resolution, respectively. Compared with other interferometers, the proposed interferometer has the advantages of simple structure, low cost and no need for mechanical scanning components.